The effectiveness of digital nudging in improving dietary quality: A systematic review of randomized controlled trials - Lan Ge; Xuewei Guan; Leiwen Tang; Qianyin Zhu; Yumei Zhong; Meijuan Lan (BMC Public Health)
Abstract Background Digital nudging is increasingly being used in the field of dietary quality change. However, existing reviews have not systematically evaluated the comparative effectiveness of different digital nudging strategies on dietary quality, particularly within the context of randomized controlled trials. Objective The objective of this study was to systematically review the scientific literature on the effectiveness of digital nudging in improving dietary quality, as observed in randomized controlled trials. Design A systematic review of randomized controlled trials. Information sources PubMed, Web of Science, Cochrane, Embase, VIP, CNKI, and Wanfang database. Methods A structured search was conducted by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The initial search spanned studies from the inception of each database to July 7, 2024, and an updated search was performed from July 8, 2024, to April 30, 2025. The Cochrane Risk of Bias 2 tool (ROB 2) was used to assess the risk of bias in the trials. Results A total of 22 trials were included in the review, with most studies showing a high risk of attrition bias. Among them, seven were conducted in the United States, 13 in Europe, and 2 in Asia, all involving adult participants aged 18 years or older. Nutritional labeling (n = 11), increased product accessibility (n = 5), framing effects (n = 4), and priming nudges (n = 1) were each associated with improvements in dietary quality. In particular, combined nudging strategies, especially the combination of labeling and availability enhancement (n = 5), demonstrated stronger effects than single nudges. The effectiveness of digital nudging interventions was also influenced by factors such as individuals’ dietary preferences, contextual settings, and socioeconomic status. Conclusions Digital nudging, particularly with nutritional labels and increasing accessibility of products, showed the most consistent positive effects, improving food choice and dietary intake. Clinical trial registration The review protocol was registered in PROSPERO under the number CRD42024560677.